ALGORITHM OF MORPHOLOGICAL SIGNS OF PNEUMONIA WITH COVID-19 - Kutlikova G. M., Sodikova D. T. (Galaxy International Interdisciplinary Research Journal, 2022)
The entire world is suffering from the pandemic of the coronavirus infection, and it has been found that the SARS-CoV-2 virus infects the respiratory tract and lungs in most cases. Active replication of the virus in the epithelium of the respiratory tract leads to acute respiratory syndrome (OO'RS) and SARS, viremia, immune disorders, hypoxia, and clinical severity in the 2nd week after infection. In order to study the pathomorphological changes that develop in the lungs, 8 people who died from coronavirus were autopsied. Under the influence of the virus, the covering epithelium of the bronchi and alveoli, blood vessels and interstitial connective tissue are damaged and destroyed, and the alveoli are affected by pathological atelectasis, dystelectasis and distress syndrome. Another feature of lung tissue damage caused by coronavirus is the proliferation of fibroblasts, which are part of the connective tissue around the bronchi, vessels and between the alveoli, resulting in interstitial fibroplastic alveolitis.